The corporation as a protagonist in global history, c. 1550-1750 - Pettigrew, William Andrew; Veevers, David (2019)
William A. Pettigrew and David Veevers put forward a new interpretation of the role Europe’s overseas corporations played in early modern global history, recasting them from vehicles of national expansion to significant forces of global integration. Across the Mediterranean, Atlantic, Indian Ocean and Pacific, corporations provided a truly global framework for facilitating the circulation, movement and exchange between and amongst European and non-European communities, bringing them directly into dialogue often for the first time. Usually understood as imperial or colonial commercial enterprises, The Corporation as a Protagonist in Global History reveals the unique global sociology of overseas corporations to provide a new global history in which non-Europeans emerged as key stakeholders in European overseas enterprises in the early modern world. Contributors include: Michael D. Bennett, Aske Laursen Brock, Liam D. Haydon, Lisa Hellman, Leonard Hodges, Emily Mann, Simon Mills, Chris Nierstrasz, Edgar Pereira, Edmond Smith, Haig Smith, and Anna Winterbottom.